Perilaku Bullying Pada Remaja Ditinjau Dari Pola Asuh Otoriter Orang Tua Dan Jenis Kelamin - Carima, Farah; , Dra. Juliani Prasetyaningrum, M. Si., Psi (2017)
This research aims to know corellation between bullying behavior in students with authoritarian parenting parents, and to show the difference in behavior of bullying be reviewed from gender. This research was conducted in one of the first high schools in the city of Surakarta. The subject in this research amounts to 89 people consisting 47 students are male and 42 students are female. Sampling is done with cluster random sampling techniques. The methods used in this research is quantitative methods with a measuring instrument in the form of scale of bullying behavior and scale of authoritarian parenting parents. Technique of data analysis with correlation Product Moment from Pearson and analysis with t-test. Based on the results of data analysis with the correlation product moment obtained coefisien correlation value (rxy) = 0.452 with taraf significance = 0.000 (p < 0.01) it means there is a positive corelation between authoritarian parenting parents with bullying behavior on students. Bullying behavior variable and authoritarian parenting parents included in low categories. Beside in addition to that of the results with either using independent sample t-test obtained the value t-test is 2.822 with taraf sig = 0.006 (p < 0.05) it means there is a difference bullying behavior between male students and female students. This research shows that male students more often do bullying behavior than female students